THEORETICAL AND METHODOLOGICAL ASPECTS FOR THE TEACHING OF VIRTUAL EXHIBITIONS: : ANALYSIS OF THE NOIA CURRICULUM EXHIBITION (Citizenship in Action: Extension and Culture Magazine, 2023)
This article deals with the analysis, planning and development of virtual exhibitions in the context of emergency remote education implemented due to the COVID-19 pandemic. Specifically, the research is anchored in the development of the curricular exhibition held in the Museology Undergraduate Course of the Federal University of Santa Catarina, resulting from the mandatory curricular discipline Practice of Exposure. The exhibition provides important analysis on shared curation, digital culture and web environment, methodological procedures for the development of virtual exhibitions and online audience research tools.
Keywords: Virtual exhibitions; Expography; Teaching; Museology; Digital Culture